SAT-LB2 Elevated Testosterone Secondary to Leydig Cell Hyperplasia in Bilateral Ovaries - Ali, Sarah (J Endocr Soc, 2020)
Background: Postmenopausal hyperandrogenism can be caused by androgen use, ovarian hyperthecosis, ovarian neoplasms, and adrenal neoplasms. Clinical case: A 64 year old post-menopausal woman presented for evaluation of hirsutism. She had developed generalized hair loss, terminal hairs on face and chest, and new onset acne after discontinuing hormone replacement therapy. During workup for hirsutism, she was found to have elevated testosterone at 119 ng/dL (reference range: 2-45 ng/dL). Other hormonal evaluation came back within normal limits, with DHEA sulfate <15 mcg/dL (reference range <186 mcg/dL), estradiol 25 pg/ml (reference range <12-32 pg/ml), FSH 34.9 mIU/ml (reference range 23-116.3 mIU/ml), and LH 30.1 mIU/ml (reference range 15.9-54 mIU/ml). Transvaginal ultrasound did not reveal any abnormal adnexal masses. CT abdomen showed a 1.0 cm nodule in the left adrenal gland consistent with a lipid rich adenoma. Further work up showed a normal 24 hour urine free cortisol at 25 ug/24h (reference range: 4-50 ug/24h), normal 24 hour urine metanephrines at 709 ug/24h (reference range: 224-832 uh/24h), normal aldosterone at 13 ng/dL (reference range <21 ng/dl) and renin at 0.37 ng/mL/h (reference range 0.25-5.82 ng/mL/h). MRI of the adrenal glands showed a slightly lobular left adrenal gland and no discrete adrenal mass. MRI of the pelvis showed mildly prominent ovaries bilaterally, but no adnexal or ovarian masses. After repeat laboratory testing showed consistently elevated testosterone levels up to 170 ng/dl and symptoms of hyperandrogenism persisted, the patient underwent bilateral salpingo-oophorectomy. Testosterone level post-operatively dropped to 18 ng/dl and remained within normal limits on repeated measurements. Her symptoms of hyperandrogenism resolved over the next several months. Surgical pathology showed endosalpingiosis, benign paratubal cysts, and confluent aggregates of Leydig cell hyperplasia in bilateral ovaries. Conclusion: Leydig cell hyperplasia is a rare cause of hypertestosteronemia that may be considered in patients with negative work up for alternative etiologies for post-menopausal hirsutism.